Obesity and lifestyle risk factors among an adult population in Legal Amazon, Mato Grosso, Brazil (2016)
Objective To evaluate the frequency of obesity and lifestyle risk factors in the population of Barra do Garças, Legal Amazon.Methodology A randomized, transversal study with 305 adults of both genders was performed. Weight, height, body mass index (BMI), waist circumference, food dietary habits, frequency of smoking and alcoholic consumption, practice of physical activity, and the physical activity level were evaluated.  Results Smoking and alcoholic consumption was higher among men compared to women. Almost 60 % of men engaged in leisure-time physical activities, whereas only 42.4 % of women practiced physical activity. Women were engaged in mostly sedentary behavior activities, such as watching television and using the computer use than men. Dietary daily intake of fruits and vegetables were higher among women compared to men (65.9 % and 51.5 %, respectively). Men were more prone to drink soft drinks than women. However, 39.4 % of men and only 3.4 % of women drank soft drinks three or more days per week. The prevalence of overweight and obesity according to body mass index (BMI) was higher in this study. 34.4 % of men and 33.7 % of women were overweight and 15.10 % and 17.50% of men and women, respectively, were classifyied as obese. Elevated values of waist circumference were found in 35.35 % of men and 70.73 % of women.Conclusión Women were more sedentary than men and had higher prevalence of abnormal waist circumference values.